Parents’ Perceived Influence of Folktales on Child’s Social Behaviour among Primary School Pupils in Odo-Otin Local Government Area, Osun State - ATOBA, Muideen Ayomide; MUHAMMED LAWAN, Hadiza (Ilorin Journal of Education, 2024)
The study investigated parents’ perceived influence of folktales on child’s social behaviour among primary school pupils in Odo-Otin LGA, Osun State. Descriptive survey research design was adopted where one research question and three hypotheses were raised. The population of the study consist of 200 parents randomly selected from the sampled area. A researcher self-constructed questionnaire titled “Parents’ Perceived Influence of Folktales on Child’s Social Behaviour” (PPIFCSB) was used for data collection. The validity of the instrument was conducted by two experts in Childhood Education and Educational Psychology, while Cronbach Alpha reliability yielded an index of 0.81. Mean and standard deviation was used to answer the research question, while t-test and Analysis of Variance were used to test the hypotheses. The findings revealed parents perceived positive influence of folktales on child’s social behaviour. There was no significant difference in parents’ perception based on gender, level of education, while there was significant difference in parents’ perception based on location. It was recommended that parents should ensure folktales is used as part of methods of teaching moral to the children so, and the use folktales to instruct, correct, and reshape children’s behaviour should be done by the parents irrespective of their level of education. Moreover, parents should ensure folktales is used to instruct and instill good moral on the children irrespective of their gender, while parents’ location should not be a determinant for the use of folktales; rather it should be maintained across all locations.